2019
DOI: 10.1038/s41467-019-10380-0
|View full text |Cite|
|
Sign up to set email alerts
|

Hypervirulent Listeria monocytogenes clones’ adaption to mammalian gut accounts for their association with dairy products

Abstract: Listeria monocytogenes ( Lm ) is a major human and animal foodborne pathogen. Here we show that hypervirulent Lm clones, particularly CC1, are strongly associated with dairy products, whereas hypovirulent clones, CC9 and CC121, are associated with meat products. Clone adaptation to distinct ecological niches and/or different food products contamination routes may account for this uneven distribution. Indeed, hypervirulent clones colonize better the intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
229
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(259 citation statements)
references
References 81 publications
(153 reference statements)
21
229
2
7
Order By: Relevance
“…Serotype 4b (lineage I) strains like ATCC19115 have a predilection for the human host but lack the ability to compete well in the food environment where lineage II strains dominate (Orsi et al ). Over and above the genetic lineage differences influencing stress adaptation, recent evidence shows that L. monocytogenes stress resistance heterogeneity exists among sublineages and clonal complexes (Maury et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Serotype 4b (lineage I) strains like ATCC19115 have a predilection for the human host but lack the ability to compete well in the food environment where lineage II strains dominate (Orsi et al ). Over and above the genetic lineage differences influencing stress adaptation, recent evidence shows that L. monocytogenes stress resistance heterogeneity exists among sublineages and clonal complexes (Maury et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the clones which are the most prevalent in human patients are also the ones most frequently associated with listeriosis in dairy cattle, and also those most associated with contaminated dairy products. This suggests that Lm virulence in human may be linked to its ability to be associated with dairy cattle (Maury et al, ). In the same way that Pascale Cossart and colleagues have shown that comparative genomics between Lm and Li can lead to the identification of multiple Lm genes involved in its pathogenic potential (Glaser et al, ), comparative genomics of multiple Lm isolates from various sources is expected to be exceptionally powerful to identify clinically relevant microbial virulence attributes.…”
Section: Uneven Virulence Of Listeria Monocytogenes Strainsmentioning
confidence: 99%
“…(Lee, Ward, Jima, Parsons, & Kathariou, ). It also shows strong propensity for the hypervirulent clone CC2 and a specific integration site but can also be encountered in diverse clones and integration sites (Lee et al, ; Maury et al, ; Pasquali et al, ). LGI2 is typically chromosomal (Kuenne et al, ; Lee et al, ), and only rarely plasmid‐borne (Hingston et al, ).…”
Section: Cadmium Resistance In Listeriamentioning
confidence: 99%
“…The distribution of LGI2 with cadA4C4 and LGI2‐1 with cadA5C5 also suggests possible associations with virulence, as these MGEs are primarily encountered in L. monocytogenes and have a propensity for the hypervirulent clones CC2 and CC1, respectively (Lee et al, ; Maury et al, ). CadA2C2 has been encountered in outbreak strains of both serotype 1/2a and 4b (Nelson et al, ).…”
Section: Cadmium Resistance In Listeriamentioning
confidence: 99%
See 1 more Smart Citation